Вдосконалення та дослідження математичної моделі відмовостійкої маршрутизації - Журавльова, А. С.; Круглова, А. О. (ХНУРЕ, 2021)
The work combined the transport level and the access level into one network, to implement a comprehensive protection of the network from various types of damage and rational allocation of resources. A study of default gateway security protocols, such as: GLBP on GNS3 simulation equipment. An analysis of the advantages and disadvantages of both the selected and improved network structure and the mathematical model and investigated default gateway protection protocols was also performed. A mathematical model for fault-tolerant routing research is selected and improved.
Keywords: модель відмовостійкої маршрутизації